Polarization dependence of SU-8 micro ring resonator - Ariannejad, Mohammad Mahdi; Amiri, Iraj Sadegh; Azzuhri, Saaidal Razalli; Zakaria, Rozalina; Yupapin, Preecha Promphan (Elsevier, 2018)
This work describes the polarization study in the optical micro ring resonator systems. The use of polymeric materials for micro ring resonator structures recently has gained major interests due to many advantages such as enabling a rapid and straightforward fabrication process. Here we report a demonstration of an optical micro ring resonators comprised of polymer material, namely SU-8. We have shown the effects of the polarizations induced by the micro ring resonator waveguide on the spectral frequency response experimentally with respect to the changes of the polarization states as ellipticity and azimuth states. The effects can be detrimental, or these can be exploited for new devices. For both throughput and drop ports of the micro ring resonator, the highest variation of Q factor occurs in azimuth polarization state. The variation of the free spectral range induced by changing the polarization state at the drop and throughput ports is in the range of 0.2–0.65 nm and 0.2–0.75 nm respectively. Furthermore, the throughput port has experienced the highest finesse at the ellipticity polarization state. The significant wavelength shift has occurred in the drop port at the wavelength 1600 nm with azimuth polarization state. Besides, the throughput port has experienced a wavelength shift incurred by both azimuth and ellipticity states. Our results have demonstrated that low-cost photonics devices made from polymers are possible alternatives for next-generation photonics.